Cuproptosis-related signature predicts prognosis, immunotherapy efficacy, and chemotherapy sensitivity in lung adenocarcinoma - Wu, Gujie; Hu, Qin; Chen, Hongyu; He, Min; Ma, Huiyun; Zhou, Lin; Xu, Kun; Ren, Hefei; Qi, Juntao (Frontiers in Oncology, 2023)
Background: Cuproposis is a novel form of programmed cell death that disrupts the tricarboxylic acid (TCA) cycle and mitochondrial biological functions, which is quite different from common cell death patterns such as apoptosis, pyroptosis, necroptosis, and ferroptosis. However, its potential connection to tumor immunity is still an open issue, especially in lung adenocarcinoma (LUAD). Method: We used machine learning algorithms to develop a cuproposis-related scoring system. Its immunological features were investigated by exploring its impact on clinical outcomes, immune checkpoint expression, and prospective immunotherapy response in LUAD patients. Furthermore, it also predicted the sensitivity to chemotherapeutic agents. The unsupervised consensus clustering was performed to more precisely identify the different Cuproposis-based molecular subtypes and to deeply explore their underlying biological functions and mechanisms of tumor immunity. Results: Our study determined the aberrant expression and prognostic relevance of cuproposis-related genes (CRGs) in LUAD. There were significant differences in survival, biological function and immune infiltration among the cuproposis subtypes. In addition, we constructed a cuproposis scoring system that could predict clinical outcomes, tumor microenvironment, and efficacy of targeted drugs and immunotherapy in patients with LUAD. After validating with large-scale data, we propose combining the cuproptosis score and immune checkpoint blockade (ICB) therapy can significantly enhance the efficacy of immunotherapy in patients with LUAD. In conclusion: The Cuproptosis score is a promising biomarker with high accuracy and specificity for determining prognosis, molecular subtypes, immune cell infiltration, and treatment options for immunotherapy and targeted therapies in patients with LUAD. It provides novel insights to guide personalized treatment strategies for patients with LUAD.